PERCEPTION STIMULUS OF STUDENTS USING SMARTPHONE WHEN LEARNING ENGLISH - Yulistianti, Hayu Dian; Rosdiana, Aliva; Candraloka, Olyvia Revalita; Haryanto, Haryanto; Putri, Aprilia Riyana (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
This study aims to determine and examine the effects of using a smartphone while learning English. Motivation, teamwork, and portability were among the effects. The researchers investigated the impact of smartphones on English language learning, a qualitative method used in this research. The study's social context comprised fourth-semester English language education students from Ftik Unisnu Jepara. Twenty students who owned smartphones were used as research subjects. The instruments of the research used Interviews and questionnaires. According to the students' perceptions, the study's findings indicated that their use of smartphones affected their motivation, mobility, and teamwork when studying English. Additionally, using a smartphone could help them learn English more effectively. The findings of this study were corroborated by Barker's idea regarding the effects of smartphone use on learning English. However, there were drawbacks to smartphone use as well. For example, students could use their devices to cheat because they were portable, had a tendency to act quickly, and eventually developed an addiction to them.